2014
DOI: 10.1016/j.hrthm.2014.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the physiologic and prognostic implications of the heart rate versus the RR interval

Abstract: Background The HR and RR interval are inversely related. Objective To determine which parameter better describes the autonomic changes that occur after exercise and which provides stronger prognostic significance. Methods Healthy volunteers (n=33) underwent sequential bicycle exercise tests with selective autonomic blockade during exercise to define the HR and RR interval changes in recovery due to parasympathetic effect, sympathetic effect, and sympathetic-parasympathetic interaction. The prognostic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…; Goldberger et al . ); (3) short‐term time constant of HRR (T30) calculated as the negative reciprocal of the slope obtained from a linear regression between the first 30 s HR data natural log‐transformed (Imai et al . ); and (4) long‐term time constant of HRR (HRRt) obtained via non‐linear regression between RR intervals and time using data from peak exercise to 300 s of recovery (Imai et al .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…; Goldberger et al . ); (3) short‐term time constant of HRR (T30) calculated as the negative reciprocal of the slope obtained from a linear regression between the first 30 s HR data natural log‐transformed (Imai et al . ); and (4) long‐term time constant of HRR (HRRt) obtained via non‐linear regression between RR intervals and time using data from peak exercise to 300 s of recovery (Imai et al .…”
Section: Methodsmentioning
confidence: 99%
“…; Goldberger et al . ). Thereafter, vagal activity continues to increase at a smaller rate, while sympathetic activity progressively decreases (Imai et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…MeanHR for the CF comparisons may be due to the reciprocal nature of these variables, that does not allow them to be directly substituted for each other [50]. Results also showed that the use of No, Low Garza et al [37] compared Strong and Very Strong CF and excluded data obtained via the Very Strong CF due to "significant difference in output" between them, although the methodology followed or results were not described.…”
Section: The Influence Of Different Correction Factors On Heart Rate mentioning
confidence: 99%